ON THE MONITORING OF THE GAS-SOLID FLOWS IN INDUSTRIAL FLUIDIZED BEDS BY USING ELECTRICAL CHARGE SENSORS - Andrade, M. F. F. de; Reis, E. dos (Revista de Engenharia Térmica, 2018)
The fluidized bed technology has been used in many industrial processes. It promotes good rates of heat, mass transfer and chemical reaction by generating high level of gas-solid mixture. However, the assurance of quality and efficiency of these processes requires the monitoring of the gas-solid flow. For this propose, there are some sensing techniques that allows generating dynamic signals from cold or hot fluidized beds. They are based on pressure fluctuations, acoustic and mechanical vibrations, electrical capacitance and on electrical charges. Electrical charge sensors were proposed originally for measuring the flow velocity in pneumatic conveying. They are composed of one or more metallic electrodes that detect electrical charges in the gas-solid flow, which are generated by particle-particle and particle-wall interaction due to triboelectric effect. In this work, such sensors are explored as a robust and inexpensive solution for the monitoring of industrial fluidized beds. However, since research investments are requested specially on the design of the sensor, concerning the flow quantity of interest and the electrification processes acting on the sensor, in this work different configurations were classified from information in literature, and other were proposed in this work concerning their use with industrial fluidized beds. Although the relation between magnitude of the detected charges and some physical quantities of the flow, such as concentration, is still not clear, other important information can be obtained by analyzing dynamic signals, as velocity or bubbles frequency, or even for identifying of the fluidization regime. It was stated that each configuration, with its own shape and arrangement, can promote or not one or other electrification process by contact, friction or induction and, therefore, each one has a different perception of the flow.